Halau Jerebu Asap: Kebijakan dan Gerakan Pro-Keadilan Lingkungan - Hotmauli Sidabalok (Soegijapranata Catholic University, 2020)
The forest fires in Indonesia already become the chronical annual issue. Beside the climate change, there are some influence factors for this issue. First is the unequal policy which stands for the oil plantation industry. Second is government has multi interpretation to consider this issue as a disaster. Third is the weakness of stakeholders to protect forest and environment. Those three factors are analysed by using the environmental justice and the movement to protect environmental concepts. This article describes some causal factors to environmental injustice on smog disaster, the efforts to minimize disaster and environmental justice movement. The movement does not only to protect human being but also the environment. The experience and awareness to the smog become the momentum for the environmental justice movement in Indonesia.